Topical delivery of chemotherapeutic drugs using nano-hybrid hydrogels to inhibit post-surgical tumour recurrence. (29th March 2021) - Liu, Chendan; Ma, Yudi; Guo, Song; He, Bingfang; Jiang, Tianyue
Abstract : A nano-hybrid oligopeptide hydrogel embedded with transfersomes is developed for topical delivery of anticancer drugs to inhibit the post-surgical tumour recurrence. Abstract : Residual microtumours after surgical resection leading to tumour relapse is one of the major challenges for cancer therapy. Herein, we developed a nano-hybrid oligopeptide hydrogel for topical delivery of a chemotherapeutic drug, docetaxel (DTX), to inhibit the post-surgical tumour recurrence. This nano-hybrid hydrogel (DTX-CTs/Gel) was prepared by encapsulating DTX in cell-penetrating peptide-modified transfersomes followed by embedment in an oligopeptide hydrogel. The obtained DTX-CTs/Gel showed paintable and injectable properties, and could support prolonged retention at the administrated sites after topical administration. DTX-CTs released from the hydrogel presented high skin and tumour penetration capabilities, and increased the accumulation of DTX in the cancer cells leading to enhanced cell death. We showed that the topical delivery of DTX using DTX-CTs/Gel efficiently slowed down the tumour relapse in post-surgical mouse melanoma and breast tumour models.